Influence of destructive leadership behaviors on the meaning of work and work productivity - Grill, Martin (Frontiers in Psychology, 2023)
This study aimed to determine the influence of destructive leadership behaviors on employees’ meaning of work and work productivity, using a longitudinal research design. Local government organizations in a municipality in Sweden were invited to participate in the study. Self-rated questionnaire data on employees’ meaning of work and work productivity was collected at four time points over a period of 18 months, and 582 employees responded to the questionnaire on one or more occasions. A 4-item Destructive Leadership Scale (DLS) was developed and used at the first time point to assess the destructive leadership behaviors of incoherent planning, assigning unnecessary tasks, ambiguous expectations, and autocratic behavior. Latent growth models were used to analyze the influence of destructive leadership on the change in employees’ meaning of work and work productivity over the 18-month period. The results show that destructive leadership has a significant negative influence on employees’ meaning of work (β = −0.44, p = 0.02) and work productivity (β = −0.46, p = 0.04). The effect sizes were greater than those identified in previous cross-sectional studies, indicating that the effects of destructive leadership may accumulate and become more important over time. Important destructive leadership behaviors include incoherent planning, assigning unnecessary tasks, ambiguous expectations, and autocratic behavior. These behaviors have a significant negative effect on employees’ meaning of work and work productivity. Proactive assessment of destructive leadership behaviors is warranted to improve future selection and training of managers.